A Subgroup Method of Projecting Future Vulnerability and Adaptation to Extreme Heat - Lee, Jae Young (Sustainability (Switzerland), 2022)
This study presents a new method, a subgroup method, of predicting future vulnerabilities to high temperatures. In this method, the total population is divided into subgroups based on characteristics such as age. The adaptation trends are extracted for each subgroup, and they are combined based on the demographic structure of the future population to obtain the overall future relative risk of mortality to heat. The subgroup method is better than a simple extrapolation method because it can consider any demographic and socio-economic changes in the population. This study predicts the future temperature-related vulnerability of South Korea until 2100 based on the subgroup method. South Korea is one of the fastest aging countries, where the portion of mortality for older population aged 75 and more in 2005 (center of the baseline period) was 42.9%, whereas the portion becomes 96.5% in 2100, dominating the total mortality. This study found that the older population aged 75 and more can adapt to extreme temperatures like 40 °C 4.5 times slower than the younger population aged under 75. In addition, this study found that the conventional simple extrapolation method assumed a constant demographic structure and overestimated the future adaptation rate by 7.1 times faster than the subgroup method, which considered the demographic change and estimated the overall future vulnerability to extreme heat accordingly. The finding in this study shows that it is very important to consider demographic changes in the future temperature-related vulnerability projection, particularly in a fast-aging country like South Korea.
Keywords: adaptation; future vulnerability; global warming; subgroup method; temperature-related mortality